Impact of Microfinance Banks on Micro and Small Enterprises in Ogun State, Nigeria - Akingunola, Richard Oreoluwa; Olowofela, Olusola Enitan; Yunusa, Lafeet (Binus Business Review, 2018)
This research investigated the impact of microfinance on Micro and Small Enterprise (MSE) in Ogun State, Nigeria. There were two research problems. First, it was whether microfinance bank (financial intermediation services) assists MSEs in Ogun State, Nigeria. Second, it was whether microfinance banks assist MSEs in improving the volume of trade they engaged in Ogun State, Nigeria. The purposive and stratified sampling method was used. The survey obtained 408 respondents in MSEs in Ogun State. The research problems were tested with simple regression analysis. Findings from the first problem show that there is a negative relationship between intermediary financial services (credit disbursement) and MSEs. The second finding also shows there is a positive relationship between microcredit and business expansion. The research concludes that businesses that access microcredit have grown averagely regarding business expansion. Therefore, it is recommended that microfinance banks should increase the size of loan and interest charged to MSEs, so they have enough funds to finance their operations. The researchers further recommend that government should review the activities of microfinance institutions.